SIMULASI PENGEMBANGAN LAPANGAN PANAS BUMI LAINEA; THE DEVELOPMENT SIMULATION OF LAINEA GEOTHERMAL FIELD - Putriyana, Lia; Soekarno, Hari (P3TKEBTKE, 2015)
Lapangan panas bumi Lainea terletak di kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara. Pada tahun 2012 Pusat Sumber Daya Geologi melakukan penyelidikan terpadu Geologi, Geokimia dan Geofisika, serta pengeboran sumur landaian suhu untuk menentukan daerah prospek. Survei geologi ditujukan untuk mendapatkan pemetaan dan gambaran struktur geologi setempat. Survei geokimia yang dilakukan mendukung eksplorasi daerah tersebut. Survei geofisika dapat mendukung pemahaman struktur bawah permukaan. Terdapat 4 sumur landaian suhu untuk mengukur temperatur aktual bawah permukaan, 3 sumur diantaranya menunjukan adanya anomali gradien temperatur sekitar area manifestasi. Kapasitas pembangkitan yang didapatkan dari hasil simulasi 2 skenario pengembangan yang berbeda sebesar 1250 kW (skenario 1, 1 sumur produksi) dan 2250 kW (skenario 2, 2 sumur produksi).Analisa dan prediksi perilaku reservoir panas bumi setiap waktu adalah hal yang penting dilakukan untuk memastikan ketersediaan fluida panas bumi yang digunakan untuk membangkitkan listrik. Informasi yang didapatkan dari survei terpadu dan pengeboran landaian suhu akan mendukung simulasi model numerik. Lainea geothermal field is located in South Konawe, South East Sulawesi. In 2012, Center of Geological Resources has conducted an integrated survey of geology, geochemistry and geophysics, and also the temperature gradien drilling to determine prospect area. The aim of the geology survey is to find out the mapping and image of the local geology structure. Geochemistry survey is a fundamental tool to support geothermal exploration, fluid and gas sampling, geothermometer, analysis of fluid patterns andalso environmental issues as a data base. Geophysics survey can improved the understanding of subsurface structure. The temperature gradient drilling or thermal gradient holes for direct measurement of field temperature have been conducted in 4 different locations, LNA-1, LNA-2, LNA-3 and LNA-4. The thermal gradient as the result of the temperature gradient drilling shows anomaly area in 3 different locations around manifestations. It provides valuable information/most reliable information on the subsurface. The capacity of the generation which obtained from the simulation result of two different development scenarios are 1250 kW (Scenario 1, one production well) and 2250 kW (Scenario 2, two production wells). The analysis and prediction of geothermal resource over time is a critical element to ensure the availability of geothermal fluid for electricity production. The information gained from this integrated survey and the temperature gradient drilling will support numerical reservoir modelling and assessment.